1992
DOI: 10.1104/pp.98.1.198
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Using Electrolyte Leakage to Assess Membrane Competence in Plant Tissues

Abstract: A new expression for ion leakage from plant tissue, the tissue ionic conductance (gT), is compared with electrical conductivity (EC) and a commonly used damage index (Id) to test the ability of each expression to correctly describe leakiness in two model systems representing examples of physiological processes with well-known effects on membrane permeability. In experiments in which drought-acclimated leaves were compared with nonacclimated leaves and senescing leaves were compared with nonsenescing leaves, Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 16 publications
4
70
1
2
Order By: Relevance
“…The electrolyte leakage was determined using the methodology described by Whilton et al (1992), by which a piece (diameter 1 cm) of damaged peel per fruit is removed. This section was washed in distilled water and surface-dried on absorbent paper, and then incubated for 2 hours in a test tube with lid, containing 18 mL of distilled water and maintained at room conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The electrolyte leakage was determined using the methodology described by Whilton et al (1992), by which a piece (diameter 1 cm) of damaged peel per fruit is removed. This section was washed in distilled water and surface-dried on absorbent paper, and then incubated for 2 hours in a test tube with lid, containing 18 mL of distilled water and maintained at room conditions.…”
Section: Methodsmentioning
confidence: 99%
“…2B). It has been known that electrolyte leakage could reflect the damage of cell membranes, and the maintenance of cell membrane integrity and stability has been reported as a major contributing factor for cold tolerance (Whitlow et al, 1992;Morsy et al, 2005). Therefore, we examined the electrolyte leakage of the overexpression plants and ZH11 during cold stress conditions.…”
Section: Identification and Expression Characterization Of Osmyb30mentioning
confidence: 99%
“…Another study suggested that maltose could protect the photosynthetic electron transport chain during cold stress treatment Guy, 2004, 2005). It has been generally accepted that the maintenance of cell membrane integrity and stability is critical for cold stress tolerance (Whitlow et al, 1992;Morsy et al, 2005), and conductivity can directly reflect damage to the cell membrane. Our results showed the relevance between maltose content and conductivity during cold stress treatment (Figs.…”
Section: Complexity Of Osmyb30 Regulation In Starch and Sugar Metabolismmentioning
confidence: 99%
“…In the present study, no CI symptoms seen until 10th day of storage, but at the day 15, CI symptoms started in all treatments, however, the cucumbers in D800 and D1600 treatments have less CI scores than the other treatments. Electrolyte leakage can be used to determine changes in membrane permeability caused by environmental stress factors such as CI [27,28]. It is therefore a useful method is measurement the K ion leakage for determining chilling damage, and it has been reported that in cucumbers, an increase in ion leakage is associated with cell damage caused by CI [29,30,31]).…”
Section: Chilling Injury Scoresmentioning
confidence: 99%